Clinical outcome of patients treated with re-irradiation for spine or pelvic bone metastasis: A multi-institutional analysis of 98 patients - Suzuki, Gen (Mol Clin Oncol, 2017)
The present study aimed to describe the clinical results of re-irradiation (Re-RT) for spine or pelvic bone metastasis at the same initial irradiated area. Between April 2010 and March 2014, cases involving 98 patients with spine or pelvic bone metastasis who had undergone Re-RT at five institutions were reviewed. The clinical outcomes following Re-RT were evaluated, including overall survival (OS) and severe adverse events. The median time interval from initial radiation therapy (RT) to Re-RT was 439 days (range, 23–4,993 days), and the median duration of patient follow-up was 256 days (range, 11–2,284 days). The median biological effective dose for the Re-RT was 150 Gy(2) (range, 17–240 Gy(2); α/β = 2). Severe late adverse events occurred in two patients who underwent three-dimensional conformal radiotherapy for lumbar spine or pelvic bone metastases, which may be associated with tumor progression. The median survival time following Re-RT was 255 days, and the actuarial OS rate at 1 year was 36%. The interval between initial RT and Re-RT, and their performance statuses (PS) were significant independent prognostic factors for OS rates in multivariate analysis. Re-RT for spine or pelvic bone metastases is a relatively acceptable option with low risk of anticipated severe adverse events, particularly for patients with good PS following a long disease-free interval.